New HPLC method to determine ethyl carbamate in alcoholic beverages using fluorescence detection - P. Herbert (2002)
A new methodology to the quantification of ethyl carbamate (EC) has been developed. This method allows the analysis by HPLC of ethyl carbarnate in samples of wine, fortified wine, and wine brandy, by a precolumn derivatization with 9-xanthydrol, and fluorescence detection. This does not require previous sample extraction or concentration. The method presents an average recovery of 96% among samples studied, a detection limit of 4.2 mug/L, and an average intermediate precision of 6.3%. The comparison of the results obtained for EC analysis on the same wine brandy samples by GC/MS and HPLC are statistically indistinguishable with 97.5% probability. The results of the analysis of 42 samples are presented.